Characterization of latently infected EBV+ antibody-secreting B cells isolated from ovarian tumors and malignant ascites - Zhang, Lixin; Strange, Mary; Elishaev, Esther; Zaidi, Syed; Modugno, Francesmary; Radolec, Mackenzy; Edwards, Robert P.; Finn, Olivera J.; Vlad, Anda M. (Frontiers in Immunology, 2024)
Introduction Intra-tumoral B cells mediate a plethora of immune effector mechanisms with key roles in anti-tumor immunity and serve as positive prognostic indicators in a variety of solid tumor types, including epithelial ovarian cancer (EOC). Several aspects of intra-tumoral B cells remain unclear, such as their state of activation, antigenic repertoires, and capacity to mature into plasma cells. Methods B lymphocytes were isolated from primary EOC tissue and malignant ascites and were maintained in cell culture medium. The stably maintained cell lines were profiled with flow cytometry and B cell receptor sequencing. Secreted antibodies were tested with a human proteome array comprising more than 21,000 proteins, followed by ELISA for validation. Originating tumor samples were used for spatial profiling with chip cytometry. Results Antibody-secreting B lymphocytes were isolated from the ovarian tumor microenvironment (TME) of four different EOC patients. The highly clonal cell populations underwent spontaneous immortalization in vitro, were stably maintained in an antibody-secreting state, and showed presence of Epstein-Barr viral (EBV) proteins. All originating tumors had high frequency of tumor-infiltrating B cells, present as lymphoid aggregates, or tertiary lymphoid structures. The antigens recognized by three of the four cell lines are coil-coil domain containing protein 155 (CCDC155), growth factor receptor-bound protein 2 (GRB2), and pyruvate dehydrogenase phosphatase2 (PDP2), respectively. Anti-CCDC155 circulating IgG antibodies were detected in 9 of 20 (45%) of EOC patients’ sera. Tissue analyses with multiparameter chip cytometry shows that the antibodies secreted by these novel human B cell lines engage their cognate antigens on tumor cells. Discussion These studies demonstrate that within the tumor-infiltrating lymphocyte population in EOC resides a low frequency population of antibody-secreting B cells that have been naturally exposed to EBV. Once stably maintained, these novel cell lines offer unique opportunities for future studies on intratumor B cell biology and new target antigen recognition, and for studies on EBV latency and/or viral reactivation in the TME of non-EBV related solid tumors such as the EOC.